(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
This article is devoted to the issue of changes taking place in modern Russian society. This paper examines the features of the development of modern society in Russia, its characteristics and features, provides various approaches to determining the development of modern society in Russia, and analyzes the prospects and trends of its development.